The Effect of the Use of Quizlet Evaluation Media on the Computational Thinking Ability of Class X Students at SMAN 1 Rambah - Yogi, Yogi; Jufri, Jufri; Muslim, Muslim; Dwiana, Ari Aprilia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the impact of using Quizlet as an evaluation tool on students' computational thinking abilities at SMAN 1 Rambah. A quantitative method with a one-group pretest-posttest design was employed, involving 36 students from class X-A selected through purposive sampling. Data were collected using computational thinking tests administered before and after the intervention. The results showed a notable increase in students' average scores, from 64.58 in the pre-test to 78.33 in the post-test. A paired sample t-test confirmed a statistically significant difference with a p-value of 0.000 0.05, indicating that Quizlet significantly enhances students' skills in decomposition, pattern recognition, abstraction, and algorithm design. These findings highlight Quizlet’s potential not only as a language learning platform but also as an effective medium for developing computational thinking in secondary education.